BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Functional characters combined with null models reveal inconsistency in mechanisms of species turnover in lacustrine fish communities - Norman W. H. Mason; Cédric Lanoiselée; David Mouillot; Pascal Irz; Christine Argillier (Oecologia, 2007)

Fish community comparisons along environmental gradients in lakes of France and north‐east USA - Pascal Irz; François Michonneau; Thierry Oberdorff; Thomas R. Whittier; Nicolas Lamouroux; David Mouillot; Christine Argillier (Global Ecology and Biogeography, 2007)
Aim To assess whether eight traits of fish communities (species richness, three reproductive traits and four trophic traits) respond similarly to environmental gradients, and consequently display convergence between the lakes of France and north‐east USA (NEUSA). Location 75 French and 168 north‐east USA lakes. Methods The data encompass fish surveys, the assignment of species into reproductive and trophic guilds, and environmental variables characterizing the lakes and their catchments. The analytical procedure was adapted from the recommendations of Schluter (1986 ) [ Ecology , 67 , 1073–1085]. Results The comparison of the regional pools of lacustrine fishes indicated that NEUSA was about twice as speciose as France, mostly due to higher species turnover across lakes, although NEUSA lakes were consistently about 20% more speciose than French lakes for a given surface area. Warmer environments were consistently inhabited by a higher proportion of phytophilous and guarder species than were colder lakes. Hence there was convergence in community reproductive traits. Conversely, there was no evidence of convergence in the trophic structure of lacustrine fish communities between regions. Main conclusions The influence of temperature on the availability and quality of spawning substrates appears to be a major constraint on present‐day lacustrine fish communities. In parallel, phylogenetic constraints, past events such as the diversification of the North American fish fauna, and selective extinctions during Pleistocene glaciations and subsequent recolonizations contribute to explaining the dissimilarities between the communities of the two regions and differences in their relationship to the environment.

Comparison between the fish communities of lakes, reservoirs and rivers: can natural systems help define the ecological potential of reservoirs? - Pascal Irz; Mélanie Odion; Christine Argillier; Didier Pont (Aquatic Sciences, 2006)

Comparison between the fish communities of lakes, reservoirs and rivers: can natural systems help define the ecological potential of reservoirs? - Pascal Irz; Mélanie Odion; Christine Argillier; Didier Pont (Aquatic Sciences, 2006)

Native and introduced fish species richness in French lakes: local and regional influences - Pascal Irz; Christine Argillier; Thierry Oberdorff (Global Ecology and Biogeography, 2004)
Aim To analyse the importance of local and regional influences on the patterns of species richness in natural and man‐made lakes and to infer the impacts of human‐mediated introductions on these patterns. Location France. Methods Species occurrence data were gathered for 25 natural and 51 man‐made lakes. Analysis is based on regression models of local richness against their related regional richness and lake environmental variables. Results Local native richness was mostly controlled by the regional richness. Conversely, local total richness was mainly explained by local variables. These statements apply to both natural and man‐made lakes. Lacustrine systems displayed weak resistance to invaders. Main conclusions Species introductions have apparently contributed to saturate fish communities in these systems even if no clear negative effect on the survival of native species (i.e. species extinction) is detectable so far.